Development Of Android Application-Based Thematic Learning Media - Muhammad Sururuddin; Ratna Indriana (Sumber Belajar Sejahtera, 2023)
This study aims to develop thematic learning media based on Android applications used the Borg and Gall development research design which consists of is simplified into 7 stages, namely: 1) potential and problems, 2) gathering information, 3) product design, 4) design validation, 5) design improvement, 6) product trial, 7) product revision. This research was conducted for class III students of MI NW 1 Kelayu. Data collected instruments include validation sheets, student response questionnaires, and teacher response questionnaires. Technical analysis of the data used in this study is a five-scale formula for validation tests, student response questionnaires, and teacher response. The results of this study indicate that the results of the media expert validation test are categorized as